Molecular and genetic characterization of the inheritance and expression of the synthetic porcine alpha-Lactalbumin transgene in maize (Zea mays L.) - Bicar, Earl H. (ProQuest Information and Learning Company, 2003)
A codon-adjusted version of a gene encoding the porcine milk protein [alpha]-lactalbumin was synthesized to create maize with improved nutritional quality. Three expression vectors (P64, P45, P57) containing the synthetic gene were constructed and transformed into maize callus by particle bombardment. The constructs differed in their promoters and subcellular targeting domains. PCR analysis showed that the [alpha]-La transgene was integrated into the maize genome and transmitted to the F1 generation. Western blot analysis indicated that the transgenes were functional and the [alpha]-La protein accumulated in the target endosperm. Genomic Southern blot analysis detected no new rearrangements demonstrating stable transgene integration pattern. The expression and inheritance patterns of the [alpha]-La transgenes were assessed. In 5 of 6 P64 events, the [alpha]-La transgene was inherited as a single locus through the F3 generation. In 5 of 6 P45 and in all 4 P57 events, irregular expression and inheritance patterns were detected. The segregation distortion was due to prevalence of kernels with no detectable [alpha]-La protein. PCR analysis of these negative kernels confirmed presence of the synthetic porcine [alpha]-La transgene, indicating that the transgene was not functional. The levels of the modified porcine [alpha]-La protein that accumulated in the endosperm as measured by ELISA ranged from 0.0014-0.095 g/100g endosperm. A significant difference in Lysine levels was detected in kernels expressing [alpha]-La when compared to their null siblings. The percent difference in Lysine content ranges from 29%-49% in both F2 and F3 generation kernels. This difference was confirmed when Lysine levels were measured by complete amino acid analysis and by a bacterial assay using E. coli auxotrophs. In addition to Lysine, significant changes in the content of other amino acids were observed such as a 24% difference in Aspartic Acid and 21.4% difference in Methionine levels. Expression of the porcine [alpha]-La did not result in substantial changes in percent total Carbon, Nitrogen and total protein content. The results demonstrated that a transgenic approach using a gene that encodes a protein such as a modified porcine [alpha]-La can be an effective strategy of improving the nutritional quality of maize grain.--Abstract.